2020
DOI: 10.15763/issn.2376-5267.2019.1.6.82-104
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of Critical Success Factors for Student-Athlete Mental Health and Wellness, Academic Success, and Athletic Performance at the NCAA Division III Level

Abstract: Current athletic administrators are not only charged with overseeing programs that are critical to student-athletes’ athletics success, but must be increasingly aware of resources to also support success in student-athletes’ academic and personal lives.  In turn, this empirical study explored the needs of student-athletes, coaches and administrators pertaining to mental health and wellness, academic success, and athletic performance at the NCAA Division III level.  Implications and recommendations are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This may reflect (a) a lack of financial/supportive resources to identify and refer student-athletes to mental health treatment within Division III schools and (b) that these typically smaller-enrollment institutions often have much higher general student UCC utilization rates than larger schools (LeViness et al, 2019). Indeed, Navarro et al (2019) demonstrated that Division III athletes, coaches, and athletic administrators share the perception of a large gap between desired and available support services for mental health, academic, and career support.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect (a) a lack of financial/supportive resources to identify and refer student-athletes to mental health treatment within Division III schools and (b) that these typically smaller-enrollment institutions often have much higher general student UCC utilization rates than larger schools (LeViness et al, 2019). Indeed, Navarro et al (2019) demonstrated that Division III athletes, coaches, and athletic administrators share the perception of a large gap between desired and available support services for mental health, academic, and career support.…”
Section: Discussionmentioning
confidence: 99%
“…Current research suggests that mental health services available to college athletes is lacking (Navarro et al, 2020). In addition to the risk of social isolation due to COVID-19, college athletes are at an elevated risk for several suicide-associated comorbidities (Thompson & Sherman, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the mental health concerns for intercollegiate athletes pre, post, and during the COVID-19 pandemic, campuses may not be equipped to handle the mental health needs of their athletes (Mawdsley, 2021). In 2020, the Journal of Higher Education Athletics and Innovation published a research article highlighting the discrepancies between services available to student athletes and services desired by student athletes and athletic staff (Navarro et al, 2020). Navarro et al (2020) provided several implications for supporting student athletes' mental health and wellbeing and urged athletic staff to "provide enhanced support services" (p. 100).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High-profile Black athletes often attend college at top-tier institutions with aspiration for high academic achievement, only to see them decline due to the intense time constraints placed on them by their coaches and sport; they become engulfed in fulfilling the role of athlete instead of student (Collins, 2018b). Consequently, conflict arises between these salient roles (Navarro et al, 2020). Bronfenbrenner (1979) describes a role as a “.…”
Section: Black Male (Athlete) Identity Development and Formationmentioning
confidence: 99%